Blockchain-based mobile application asset management - Kew, Yoong Wei (Nanyang Technological University, 2021)
Legacy and inefficient inventory management tools can impact organisations’ performance, and these systems may not meet today’s modern industry standards, in terms of productivity. Legacy system refers to system that uses outdated technologies which might run only in a specific environment but remain functional and are critical to operational needs. Such system poses integration problem as newer technology emerges and should be adopted to meet the ever-increasing demands of higher productivity. This project presented an alternative approach to inventory management and as a motivation for individuals or organisations to adopt modern digital solution by delivering an inventory management mobile application. To demonstrate a complete system structure, blockchain technology was integrated to serve as a decentralised storage (back-end technology stack) and set up of load-balancing/proxy function to facilitate mobile clients’ requests to the backend services. This report also outlined the application design, system architecture and implementation details. Various aspects of Ethereum component, such as Ethereum’s block structure and initialisation of Ethereum node, were discussed.